LOOKING AT CHILD SEXUAL ABUSE: A THEORETICAL REVIEW OF ISLAMIC EDUCATION PERSPECTIVE - Almu'faro, Ahmad Baha'uddin (ANDRAGOGI, 2024)
The high rate of sexual violence against children is still an ongoing problem and needs attention. A special and in-depth study is needed to determine solutions and strategies to reduce the risk of this case continuing. This study was written with the aim of examining how Islamic education as the basis of religious education presented in formal schools views the high number of cases of sexual violence against children. This study uses a qualitative approach with a literature review type. Data were collected from various relevant sources. Data analysis techniques were carried out by collecting the data found, categorizing it, analyzing it, then reviewing it in a discussion. The results of this study indicate that Islamic education recommends synergy and cooperation between parents, educators in schools, and the community in protecting and overcoming problems that arise in victims of sexual violence against children. In addition, Islamic education also recommends contextualization of learning, dialogical relationships between teachers and students, internalization and implementation of anti-violence values in students, teachers and school staff, and implementation of anti- violence regulations for all parties in schools. The results of this study can ultimately be used as a basis for policy making in implementing an educational process that is full of anti-violence values.